Perancangan Penilaian Kinerja Karyawan pada PT Glori Global Sukses - Yuswardi, Yuswardi; Tan, Cristina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2024)
This activity was carried out with the aim of helping PT. Glori Global is successful in facing its main problem, namely that there is no employee performance assessment. The method used in carrying out this activity is the interview method and the observation method which is carried out directly by visiting the location. This goal has been achieved with the results of the implementation of activities, namely having succeeded in creating a performance assessment form using the Management By Objective (MBO) method where division managers stated that by assessing employee performance, there was a positive increase in the company's operational efficiency, team productivity increased, and the relationship between management and employees becomes stronger.